Efficacy and safety of a single occipital nerve blockade in episodic and chronic cluster headache: A prospective observational study. (August 2017) - Gaul, Charly; Roguski, Jana; Dresler, Thomas; Abbas, Hind; Totzeck, Andreas; Görlinger, Klaus; Diener, Hans-Christoph; Weber, Ralph
Background: Treatment options for cluster headache (CH) include acute, transitional and prophylactic strategies. We assessed the efficacy and safety of a single occipital nerve block (ONB) in patients with episodic (eCH) and chronic CH (cCH). Methods: In this prospective, observational study 101 CH were treated with a single ONB using triamcinolone 10 mg and bupivacaine. Attack frequency, pain intensity and side effects were assessed at days 1 and 7 after ONB and thereafter weekly for 60 days until recurrence of attacks. Results: Baseline mean daily attack frequency was 2.9 ± 2.5 (eCH) and 3.3 ± 2.9 (cCH), which was reduced to 0.7 ± 1.2 (eCH) and 1.1 ± 1.4 (cCH) after one day ( p  = 0.08 for group difference) and to 1.1 ± 1.6 (eCH) and 1.9 ± 2.3 (cCH) after seven days ( p  = 0.01 for group difference). In patients with eCH the pain-free period lasted longer compared to cCH ( p  = 0.004). There was no association between the presence of local anesthesia and treatment response ( p  = 0.88). No serious adverse events occurred. Conclusion: ONB is an easy, safe and effective transitional treatment option in case of insufficient response of CH to treatment both in patients with eCH and cCH. Patients with eCH have a better and more sustainable treatment response.